Efek Duty Cycle Pwm pada Pengendalian Kecepatan Motor BLDC 3 Phasa - Rozlinda Dewi (Universitas Batanghari Jambi, 2018)
Nowadays almost all electric convertible equipments are in motion using Brushless Direct Current (BLDC) motors, because BLDC motors have high efficiency and energy density because the lack of brush makes BLDC motors reliable enough, maintenance is cheap and can be used for high speed. This research is more emphasized on the controller unit using DRV 11873 IC which has EVM (Evaluation Module) as strong magnetic induction enhancer in BLDC motor winding (stator) with Pulse Width Modulation (PWM) duty cycle mode, the result of research shows the relationship between the addition of duty cycle PWM and the addition of a large supply voltage V (V) given to the 3 phase Phas motor BLDC to the motor speed change (RPM). Through the calculation of coefficient of determination (R2) each experimental results between the change of power supply voltage (V) to the speed (RPM) obtained 0.998 and the calculation of coefficient of determination (R2) change duty cycle PWM signal to the speed (RPM) 0.996.